Aqueous Two-Phase Interfacial Assembly of COF Membranes for Water Desalination - Wang, Hongjian; Zhao, Jiashuai; Li, Yang; Cao, Yu; Zhu, Ziting; Wang, Meidi; Zhang, Runnan; Pan, Fusheng; Jiang, Zhongyi (Nano-Micro Letters, 2022)
Aqueous two-phase system features with ultralow interfacial tension and thick interfacial region, affording unique confined space for membrane assembly. Here, for the first time, an aqueous two-phase interfacial assembly method is proposed to fabricate covalent organic framework (COF) membranes. The aqueous solution containing polyethylene glycol and dextran undergoes segregated phase separation into two water-rich phases. By respectively distributing aldehyde and amine monomers into two aqueous phases, a series of COF membranes are fabricated at water–water interface. The resultant membranes exhibit high NaCl rejection of 93.0–93.6% and water permeance reaching 1.7–3.7 L m−2 h−1 bar−1, superior to most water desalination membranes. Interestingly, the interfacial tension is found to have pronounced effect on membrane structures. The appropriate interfacial tension range (0.1–1.0 mN m−1) leads to the tight and intact COF membranes. Furthermore, the method is extended to the fabrication of other COF and metal–organic polymer membranes. This work is the first exploitation of fabricating membranes in all-aqueous system, confering a green and generic method for advanced membrane manufacturing. Highlights: 1 All-aqueous phase approach to membrane fabrication is invented for the first time. 2 Interfacial tension of water-water interface has pronounced effect on the evolution of membrane structures. 3 Covalent organic framework membranes through aqueous two-phase interfacial assembly exhibit high water desalination performances.